Touch-me-not [large type] - Riggs, Cynthia (Riggs, Cynthia. Martha's Vineyard mysteries., 2011)
LeRoy Watts, owner of Watts Electrical, is waiting for his twin sons to come home when a recently fired employee staggers in and threatens to blackmail him. Watts shoots him with a supposedly non-lethal Taser, and he dies. Meanwhile, several members in a local knitting group are being stalked by telephone. One of them is Victoria Trumbull's granddaughter, and the 92-year-old sleuth sets out to investigate both situations.